1997
DOI: 10.1007/s004200050165
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology and surveillance of blood lead in Taiwan (R.O.C.): A report on the PRESS-BLL project

Abstract: To monitor the lead hazards in industries and to investigate the prevalence of elevated blood lead levels (BLLs) in lead-exposed workers, a lead surveillance system (PRESS-BLLs) has been established and operated in Taiwan, Republic of China, since July 1993. A cohort of lead-exposed workers who received a periodic annual health examination at 55 accredited hospital laboratories was constructed. A total of 9807 separate BLL measurements were reported to the system in 1994. The mean BLL was 15.8 micrograms/dl in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The mean blood lead level in the general Taiwanese population is 8.6 µg/dl in males and 6.7 µg/dl in females (Wu et al, 1997). A subsequent report showed that the mean blood lead level in children in Kao-Hsiung City was 5.50 µg/dl (Wang et al, 2002).…”
Section: Discussionmentioning
confidence: 98%
“…The mean blood lead level in the general Taiwanese population is 8.6 µg/dl in males and 6.7 µg/dl in females (Wu et al, 1997). A subsequent report showed that the mean blood lead level in children in Kao-Hsiung City was 5.50 µg/dl (Wang et al, 2002).…”
Section: Discussionmentioning
confidence: 98%
“…Workers exposed to lead were identified from the occupational blood-lead notification system, the Program to Reduce Exposure by Surveillance System-Blood Lead Levels (Press-BLLS) [Wu et al, 1997]. The surveillance system overseen by the Center for Disease Control, a division of the Department of Health, was primarily designed for regular monitoring of workers exposed to lead and who, by law, should be examined annually.…”
Section: Data Sourcesmentioning
confidence: 99%
“…The examination of PbBs was performed in the 55 accredited hospital laboratories routinely evaluated by the Department of Health. The interlaboratory coefficient of variation was about 15% for PbBs <20 mg/dl and about 10% for PbBs !20 mg/dl [Liou et al, 1995;Wu et al, 1997].…”
Section: Data Sourcesmentioning
confidence: 99%